8th International conference on management and rehabilitation of chronic respiratory failure: the long summaries – Part 3. Issue 1 (December 2015) - Ambrosino, Nicolino; Casaburi, Richard; Chetta, Alfredo; Clini, Enrico; Donner, Claudio; Dreher, Michael; Goldstein, Roger; Jubran, Amal; Nici, Linda; Owen, Caroline; Rochester, Carolyn; Tobin, Martin; et al.
Abstract This paper summarizes the Part 3 of the proceedings of the 8th International Conference on Management and Rehabilitation of Chronic Respiratory Failure, held in Pescara, Italy, on 7 and 8 May, 2015. It summarizes the contributions from numerous experts in the field of chronic respiratory disease and chronic respiratory failure. The outline follows the temporal sequence of presentations. This paper (Part 3) presents a section regarding Moving Across the Spectrum of Care for Long-Term Ventilation (Moving Across the Spectrum of Care for Long-Term Ventilation, New Indications for Non-Invasive Ventilation, Elective Ventilation in Respiratory Failure - Can you Prevent ICU Care in Patients with COPD?, Weaning in Long-Term Acute Care Hospitals in the United States, The Difficult-to-Wean Patient: Comprehensive management, Telemonitoring in Ventilator-Dependent Patients, Ethics and Palliative Care in Critically-Ill Respiratory Patients, and Ethics and Palliative Care in Ventilator-Dependent Patients).